Nucleotide sequence, mutational analysis, transcriptional start site, and product analysis of nov, the gene which affects Escherichia coli K-12 resistance to the gyrase inhibitor novobiocin. - Ivanisevic, R (1995)
In a previous study, we demonstrated the existence of a gene locus, nov, which affects resistance of Escherichia coli K-12 to the gyrase inhibitor novobiocin and, to a lesser degree, coumermycin (J. Rakonjac, M. Milic, D. Ajdic, D. Santos, R. Ivanisevic, and D. J. Savic, Mol. Microbiol. 6:1547-1553, 1992). In the present study, sequencing of the nov gene locus revealed one open reading frame that encodes a protein of 54,574 Da, a value. found to be in correspondence with the size of the Nov protein identified in an in vitro translation system. We also located the 5' end of the nov transcript 8 bp downstream from a classical sigma70 promoter. Transcription of the gene is in the counterclockwise direction on the E. coli chromosome. Transposon mutagenesis of nov followed by complementation analyses and replacement of chromosomal alleles with mutated nov confirmed our previous assumption that the nov gene exists in two allelic forms and that the Novr gene is an active allele while the Novs gene is an inactive form. After comparing nucleotide sequences flanking the nov gene with existing data, we conclude that the gene order in this region of the E. coli K-12 map is att phi 80-open reading frame of unknown function-kch (potassium channel protein)-nov-opp. Finally, the possible identity of the nov gene with cls, the gene that codes for cardiolipin synthase, is also discussed.